2020
DOI: 10.3390/jcm9030886
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biomarkers in Patients with Chronic Kidney Disease: An Analysis of Patients Enrolled in the GCKD-Study

Abstract: Background: Chronic kidney disease (CKD) and cardiovascular diseases (CVD) often occur concomitantly, and CKD is a major risk factor for cardiovascular mortality. Since some of the most commonly used biomarkers in CVD are permanently elevated in patients with CKD, novel biomarkers are warranted for clinical practice. Methods: Plasma concentrations of five cardiovascular biomarkers (soluble suppression of tumorigenicity (sST2), growth differentiation factor 15 (GDF-15), heart-type fatty acid-binding protein (H-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 71 publications
1
20
0
2
Order By: Relevance
“…Except LN, IGFBP-2 in the blood can be used as an early diagnostic marker for AKI, and its sensitivity is higher than creatinine, urea nitrogen and cystatin C ( Li et al, 2018 ), and this might be induced by hypoxia ( Minchenko et al, 2015 ). In studies related to chronic kidney disease, circulating IGFBP-2 increased in CKD patients with different conditions, including experimental uremia, CKD caused by heart failure, and children with CKD ( Powell et al, 1996 ; Tönshoff et al, 1997 ; Mahesh and Kaskel, 2008 ; Narayanan et al, 2012 ; Mirna et al, 2020 ; Ravassa et al, 2020 ). What’s more, clinical studies have also tracked the renal function level and plasma IGFBP-2 concentration of more than 400 patients with diabetic nephropathy over an 8-year period, suggesting that IGFBP-2 is a biomarker to predict longitudinal deterioration of renal function in patients with type 2 diabetes ( Narayanan et al, 2012 ).…”
Section: Igfbp-2mentioning
confidence: 99%
“…Except LN, IGFBP-2 in the blood can be used as an early diagnostic marker for AKI, and its sensitivity is higher than creatinine, urea nitrogen and cystatin C ( Li et al, 2018 ), and this might be induced by hypoxia ( Minchenko et al, 2015 ). In studies related to chronic kidney disease, circulating IGFBP-2 increased in CKD patients with different conditions, including experimental uremia, CKD caused by heart failure, and children with CKD ( Powell et al, 1996 ; Tönshoff et al, 1997 ; Mahesh and Kaskel, 2008 ; Narayanan et al, 2012 ; Mirna et al, 2020 ; Ravassa et al, 2020 ). What’s more, clinical studies have also tracked the renal function level and plasma IGFBP-2 concentration of more than 400 patients with diabetic nephropathy over an 8-year period, suggesting that IGFBP-2 is a biomarker to predict longitudinal deterioration of renal function in patients with type 2 diabetes ( Narayanan et al, 2012 ).…”
Section: Igfbp-2mentioning
confidence: 99%
“…A head-to-head comparison study with Gal-3 in patients with chronic heart failure also demonstrated that sST-2 performed better than Gal-3 and could predict 5-year risk of cardiovascular death (Bayes-Genis et al, 2014). The significant correlation between plasma sST-2 levels and the progression of CKD to ESRD was also confirmed in a recent cohort study involving 219 patients who participated in the German Chronic Kidney Disease (GCKD) study (Mirna et al, 2020). All the evidence demonstrated the importance of sST-2 in evaluating the cardiovascular risk of CKD.…”
Section: Soluble St-2mentioning
confidence: 77%
“…Growth differentiation factor-15 (GDF-15) is a member of the transforming growth factor beta cytokine superfamily, and its expression may be induced in response to ischemia. GDF-15 was significantly associated with increased risk of CKD progression in several studies [124][125][126][127]. Nair et al (2017) showed that circulating GDF-15 levels were strongly correlated with intrarenal expression of GDF-15, stating that GDF-15 may be a marker for intrarenal signaling pathways associated with CKD development and progression [124].…”
Section: Biomarkers Of Inflammationmentioning
confidence: 99%